Release of Pen-reared Bobwhites: Potential Consequences to the Genetic Integrity of Resident Wild Populations - Kristine O. Evans; Mark D. Smith; Loren W. Burger Jr.; Rachel J. Chambers; Allan E. Houston; Rick Carlisle (National Quail Symposium Proceedings, 2017)
In response to low encounter rates with wild northern bobwhite (Colinus virginianus; hereafter bobwhite) during bird dog field trials at Ames Plantation in Tennessee, a large-scale release program of pen-reared bobwhites was implemented in fall 2002. To evaluate genetic effects of pen-reared releases on wild populations, we monitored survival of pen-reared and wild bobwhites from fall release of pen-reared bobwhites through the breeding season and collected feather samples from wild, pen-reared, and free-ranging juvenile bobwhites following the first breeding season after the initial release. We used genotypes from 6 polymorphic microsatellite loci to measure genetic diversity and conduct population assignment tests. Wild bobwhites experienced greater fallspring and annual survival than pen-reared bobwhites; however, pen-reared bobwhites experienced greater fall-spring and annual survival than reported in most other studies. Genetic diversity, number of alleles, and allelic richness were greatest in the wild, intermediate in the F1 generation, and lowest in the pen-reared populations. Likelihood analysis and cluster analysis indicated 20.4% and 33.6%, respectively, of juveniles captured after the first breeding season following release were ambiguous in population assignment; suggesting successful reproduction between wild and pen-reared individuals. These results suggest that large-scale releases of pen-reared bobwhite may result in negative impacts on genetic integrity of resident wild populations.
Keywords: Ames Plantation; Colinus virginianus; genetic variability; hybridization; microsatellites; northern bobwhite; pen-reared; survival; Tennessee